Modeling Tide And Storm Surge In The East Coast Of Peninsular Malaysia [QA911. L923 2007 f rb]. - Loy, Kak Choon (2007)

(untitled)
The primary focus of this thesis involves the numerical simulations of the hydrodynamic flows in the coastal areas of Terengganu, which is subjected to tides and the two seasonal monsoons.